Data Integration among Sensor Nodes Using Wireless Toolkit (International Journal of Engineering and Computer Science, 2017)
: Network level privacy can be categorized into four sub categories: Identity, route, location and data pivacy.It is so challenging to achieve complete network level privacy due to the constraints like energy, memory and computation power imposed by the sensor nodes and constraints like mobility and topology imposed by the sensor networks and QOS issues like packet reachability and timeliness. In this paper we proposed a new identity routing and location algorithm that provides additional reliability and data privacy.This proposed solution protects the data from various privacy attacks such as eavesdropping and hop-by-hop trace back attacks.